Effect of a Community‐Based Service Learning Experience in Geriatrics on Internal Medicine Residents and Community Participants. Issue 9 (22nd July 2017) - Miller, Rachel K.; Michener, Jennifer; Yang, Phyllis; Goldstein, Karen; Groce‐Martin, Jennine; True, Gala; Johnson, Jerry
Abstract : Community‐based service learning (CBSL) provides an opportunity to teach internal medicine residents the social context of aging and clinical concepts. The objectives of the current study were to demonstrate the feasibility of a CBSL program targeting internal medicine residents and to assess its effect on medical residents and community participants. internal medicine residents participated in a CBSL experience for half a day during ambulatory blocks from 2011 to 2014. Residents attended a senior housing unit or center, delivered a presentation about a geriatric health topic, toured the facility, and received information about local older adult resources. Residents evaluated the experience. Postgraduate Year 3 internal medicine residents (n = 71) delivered 64 sessions. Residents felt that the experience increased their ability to communicate effectively with older adults (mean 3.91 ± 0.73 on a Likert scale with 5 = strongly agree), increased their knowledge of resources (4.09 ± 1.01), expanded their knowledge of a health topic pertinent to aging (3.48 ± 1.09), and contributed to their capacity to evaluate and care for older adults (3.84 ± 0.67). Free‐text responses demonstrated that residents thought that this program would change their practice. Of 815 older adults surveyed from 36 discrete teaching sessions, 461 (56%) thought that the medical residents delivered health information clearly (4.55 ± 0.88) and that the health topics were relevant (4.26 ± 0.92). Free‐text responses showed that the program helped them understand their health concerns. This CBSL program is a feasible and effective tool for teaching internal medicine residents and older adults.